The Role of Artificial Intelligence (AI) in Improving the Quality of Education in Early Childhood Education Programs - Mariaulfah Ulfa; Shahzadi Hina (Al-Qalam Institute, 2025)
The purpose of this study is to examine the role of artificial intelligence (AI) in improving the quality of early childhood education (PAUD). This study reviews relevant journals, books, and other academic sources using a qualitative approach to literature research. The findings indicate that AI can significantly enhance the quality of PAUD by facilitating access to educational content and providing personalized learning experiences. AI technologies, such as visual mentors, voice assistants, intelligent content, and personalized learning platforms, support early childhood development and can adapt to children’s individual needs. AI applications like ChatGPT, Kahoot, and Animaker also contribute to interactive and adaptive learning environments, making learning more engaging and efficient. By utilizing AI, PAUD can offer more compelling content delivery, improve the stimulation of child development, and introduce children to digital tools in an age-appropriate way. This allows for a more meaningful learning experience that fosters early digital literacy and supports adaptive learning processes.